MODERNITAS DAN MEDIA: ISU NASIONALISME - Sulkhan Chakim (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2012)
This study focuses on the power and influence of mass media in relation to themodernity in Indonesia. Some of the key media theories are related to issues of modernityand nationalism in Indonesia. The description of historical facts always contains aninherent bias with technologies related to the use of media-related time or space. Both arebased on the political and economical interest.Some of the strategies in the discourse and praxis of nationalism in the form ofpragmatic interests, consensus can not be realized then what happens is done in a waycompromises tolerate arguments and ethical-political beliefs and find a balance. actualmass media as a new technology can strengthen and pasting various elements of thenation that can be imagined through the messages of national language and strengthennationalism. Both became major elements of discourse in producing the realization ofintegration and political legitimacy in the context of the Unitary Republic of Indonesia(NKRI).